Evaluation of the Aerospray 7721 automatic acid-fast staining instrument - SANO, Mai; KAWAKAMI, Takaaki; NAKAMURA, Ayako; MISAWA, Shigeki; CHONAN, Masayoshi; MIIDA, Takashi; HORII, Takashi; OHSAKA, Akimichi (Japanese Journal of Medical Technology, 2020)
In this study, we evaluated the performance of Aerospray 7721, an automated acid-fast staining instrument. Four fixed smear slides from 17 specimens positive for acid-fast bacteria (AFB) were examined by five different methods: that recommended by the Aerospray 7721 manufacturer (original method); two methods using modified decolorizer solutions; a heating method, in which smear slides were heated immediately prior to staining with Aerospray 7721; and the Ziehl-Neelsen method (reference method). AFB counts were consistent between the original and reference methods in 8 of the 17 specimens examined (47.1%); in the remaining nine specimens, bacillus counts obtained by the original method were lower. Five specimens with lower AFB counts were categorized as negative by the original method. The decolorizer solution modifications included (1) changing the concentration of nitric acid from 2 to 1%, and (2) using isopropyl alcohol instead of ethanol. The results obtained by these modified decolorizer methods were similar to those obtained by the original method. Heating the smear slides prior to staining produced results similar to those of the reference method. For each method, AFB counts were compared between experienced (four observers, ≥3 years of experience) and inexperienced (four observers, < 6 months of experience) technologists. Among the inexperienced technologists, the heating method produced the best results, approaching those of the reference method. The results of this study demonstrate that Aerospray 7721 can stain mycobacteria as successfully as the Ziehl-Neelsen method when heat is applied to the smear slides immediately prior to staining and is therefore an appropriate technique for routine mycobacteriological tests.